Author Response: Oral and Topical Treatment of Painful Diabetic Polyneuropathy: Practice Guideline Update Summary: Report of the AAN Guideline Subcommittee. (22nd November 2022) - Callaghan, Brian C.
Abstract : We are grateful for the response to this guideline summary. 1 Dr. Argoff makes the important point that many patients with painful diabetic neuropathy continue to experience pain despite using the recommended medications. This highlights the need for new therapies for this common and highly morbid condition. He also points to 2 recent articles, both examining the same trial at different time points, that evaluated the efficacy of 10 kHz spinal cord stimulation (SCS) for patients with painful diabetic neuropathy. 2, 3 This AAN guideline was focused on oral and topical medications; therefore, devices such as SCS were not included. 4 However, it should be pointed out that the recent studies of 10 kHz SCS were not blinded, which is extremely important when rating the evidence for clinical trials with pain outcomes. As a result, future studies with appropriate sham controls are needed before including these interventions in future guideline recommendations.